Community implementation of a brief parent mediated intervention for toddlers with probable or confirmed autism spectrum disorder: feasibility, acceptability, and drivers of success (IE Drmic et al.) - Drmic, Irene; Brian, Jessica; Roncadin, Caroline; Shaver, Chantelle; Pase, Marlene; Rugajs, Natalie; Tofano, Kristina; Dowds, Erin; Zwaigenbaum, Lonnie; Smith, Isabel M.; Bryson, Susan E. (Frontiers in Pediatrics, 2024)
Background. Social ABCs is a caregiver-mediated Naturalistic Developmental Behavioral Intervention for toddlers with confirmed/suspected Autism Spectrum Disorder (ASD), with evidence in controlled research settings (Brian et al., 2017). Information is lacking on implementation in community settings (Vivanti et al., 2017). We reported on the treatment effectiveness of this program within a community setting (Brian, Drmic et al., 2022), and the current paper describes the implementation phase of this work. Distinguishing between treatment and implementation effectiveness is critical for transporting interventions from laboratory to community (Proctor, 2009). Objectives. Describe the implementation of Social ABCs through a large public autism service, supported by a research-community partnership (Stahmer et al., 2019; Vivanti et al., 2018). Methods. We describe this project through the Exploration, Preparation, Implementation, Sustainment (EPIS) framework as it focuses on implementation of evidence-based practices in publicly funded services (Aarons et al., 2011; Moullin et al., 2019). We apply this framework to the reporting stage (Moullin et al., 2019). This project took place in the context of a 3-year government-funded pilot at a hospital-based publicly funded autism service. Participants: Program developers; Autism Service team; toddlers with suspected/confirmed ASD aged 14-34 months (M = 25.18 months) and their caregivers. Training/supervision: Provided by program developers at tapering intensity. Evaluation: Caregivers completed the Caregiver Diary and satisfaction surveys. We explored training processes, intervention uptake, acceptability, adaptations to fit community context, appropriateness, perceived impact, and facilitators/barriers. Results. Six coaches were trained to fidelity, and three of these were further trained as Site Trainers. 183 clinically referred families enrolled and 89.4% completed the 12-week program. Caregivers reported increases in adherence and competence, high satisfaction and perceived benefits for their children. Coaches reported high satisfaction. Toddlers were appropriately identified to receive the intervention. Referral processes improved, including decreased referral age, and increased family readiness for diagnostic assessment and subsequent services. Conclusions. Social ABCs was successfully implemented in a community service through a research-community partnership. The program was feasible, acceptable, and appropriate within a community context. Drivers of success included funding, institutional support, shared decision-making, adaptations to fit context, leadership support, perceived positive impact, and commitment to evaluation.